Independent inheritance of Striga and Alectra resistance in cowpea genotype B301 - Atokple, I.; Singh, B.; Emechebe, A. (1993)
Cowpea [Vigna unguiculata (L.) Walp] is a major food legume the semi-arid region of Sub-Saharan Africa. Recently, two parasitic weeds, Striga [Striga gesnerioides (Willd.) Vatke] and alectra [Alectra vogelii Benth.] have become a major threat to cowpea cultivation in this region. A landrace of cowpea from Botswana, B301, is resistant to both parasites and genetic studies have revealed a single dominant gene for striga resistance and duplicate dominant genes for alectra resistance. This study was undertaken to ascertain whether the genes controlling resistance to these parasitic weeds are independent of each other. Genotype B301 was crossed to a susceptible variety, IT84S- 2246-4, and F1, F2, and backcross plants were screened for joint infection by pot culture technique. Roots of each plant were washed free of soil 10 wk after planting and examined for the attachment of striga and alectra. All plants of B301, and F1 and backcross plants involving B301, were completely free of striga and alectra attachments, whereas all plants of IT84S-2246-4 were infected by both parasites. The F2 generation segregated into 349 resistant to both, 118 susceptible to striga and resistant to alectra, 15 susceptible to alectra and resistant to striga, and 8 susceptible to both striga and alectra, which fit a trigenic segregation ratio of 45: 15:3:1. Backcross F1 plants involving IT84S-2246-4 segregated in a ratio of 3:3:1:1. The data indicated that genes conferring resistance to striga and alectra in B301 are non-allelic and independent of each other.